Utility of Anteroposterior Diameter Ratio of Tumor and Abdomen for Laparoscopic Approach for Radical Nephrectomy in Large Renal Masses. Issue 4 (October 2017) - Yadav, Priyank; Srivastava, Devarshi; Arakere, Sachin; Gupta, Shashikant; Aga, Pallavi; Mandhani, Anil
Introduction: Laparoscopic radical nephrectomy (LRN) is now increasingly done for tumors larger than 10 cm. Despite selection of favorable cases, LRN may not be successful due to lack of adequate working space with large tumors. We describe a new feature on Contrast Enhanced Computed Tomography (CECT) abdomen to predict feasibility of LRN for large renal masses between 10 and 15 cm. Methods: From January 2005 to December 2015, renal tumors between 10 and 15 cm were selected retrospectively for LRN. Patients with retroperitoneal lymphadenopathy, Inferior vena cava (IVC) thrombus and involvement of adjacent organs were excluded. Anteroposterior (AP) diameter ratio of renal tumor and abdomen (APROTA) was calculated by dividing the maximum AP diameter of tumor along with normal renal parenchyma, by the AP diameter of abdomen on CECT. The patients were stratified into two groups: Group A (successful LRN) and Group B (conversion to open surgery) and outcomes were compared. The reasons for conversion were also noted. Results: Of 29 patients, 16 (55.2%) had successful LRN (Group A), while 13 (44.8%) had conversion to open surgery (group B). The median tumor size in Group A was 11.3 ± 1.8 cm and in Group B was 13.6 ± 1.26 cm. Eleven of 13 patients had conversion due to large tumor size causing failure to progress. Two conversions were due to bleeding and injury to the colon each. There was a significant difference in the APROTA in group A and B [0.43 ± 0.09 in group A and 0.64 ± 0.14 in group B (p = 0.0001)]. Conclusions: Patients with APROTA of more than 0.65 are unlikely to have successful outcome with LRN.